READERS’ CHOICES. (Foreign Policy)
The article lists few global thinkers, as selected by the periodical's readers, as of January 2019, including Audrey Tang, Digital Minister of Taiwan; Moon Jae-in, President of South Korea; and Joey Joleen Mataele, LGBT rights activist.